Agent-based modeling for ex ante assessment of tree crop innovations: Litchis in northern Thailand - Pepijn Schreinemachers (2018)
This study uses an agent-based model for ex ante assessment of agricultural innovations. The model builds on whole farm mathematical programming (MP) and extends the methodology with a spatial representation of the system, the heterogeneity of farm households and landscapes, and the interaction between farm households. We apply the model in a northern Thai watershed to study the potential of four innovations to increase the profitability of litchi orchards. Cost-benefit analysis shows that each innovation would increase the profitability of litchi growing; however, the results of the agent-based model show that at current price levels these innovations alone would not be enough to stem the decline in the area under litchis. The model was validated and the sensitivity of the results tested for variations in the irrigated water supply and liquidity. We report on how farmers responded to these results and discuss the implications for other areas in northern Thailand. © 2010 International Association of Agricultural Economists.